INCREASING THE STUDENTS’ VOCABULARY MASTERY THROUGH SONGS A STUDY CONDUCTED AT THE “ETTY” TONDANO ORPHANAGE - Darmawan, I Made; Palenkahu, Noldy; Rorimpandey, Rinny (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
English is one of the most important languages in the world. It can because as a language in any part of the world. That is why it is taught at all levels of education in our country, Indonesia. The purpose of the research was to find out whether the use of songs could increase the student’s mastery of vocabulary or not. In conducting this research, quantitative research was used. The subject of this study were the childrens at the “ETTY” TondanozOrphanage which consisted of 20 children. The instrument of collecting data was in the form pre-test and post-test. The tests were in the form fill-in test with missing words. The result of this research showed that the mean scores in the post-test was higher (80) than those of pre-test (46). It could be concluded that, the use of song was effective to increase student’s vocabulary mastery because it could be stimulated students in learning and encourage them to be able to memorize the word.from the conclusions above,hopefully in the future this method will often be applied in the teaching and learning process so that it is easier for students to increase vocabulary